PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 2 TILATANG KAMANG - Alifah, Dara Mega (Jurnal Edukasi dan Penelitian Matematika, 2024)
In order for students to solve issues in a variety of real-life contexts using mathematical concepts and abilities, they must have a strong grasp of mathematical literacy. The observations made throughout the PLK period and the early evaluations at SMPN 2 Tilatang Kamang show that class VIII students' competency level is still fairly low. An effective strategy for dealing with this problem is to apply the Problem Based Learning method. The One Group Pretest-Posttest Design was used as a pre-experimental design in this study to look at how the PBL learning model affected math literacy. Researchers wanted to see how well participants did both before and after using the PBL approach of instruction. A significant result (2-tailed) of P = 0.001 was produced by the hypothesis test, which utilized the paired sample t-test using SPSS. Students' mathematical literacy levels were significantly different on the pretest and posttest. Students' mathematical literacy can be improved by the adoption of the PBL paradigm, as evidenced by the moderate level of improvement (0.59) in the N-Gain exam.Keywords– Mathematical Literacy Ability, Problem Based Learning